Innate immune memory of tissue‐resident macrophages and trained innate immunity: Re‐vamping vaccine concept and strategies. Issue 3 (3rd March 2020) - Xing, Zhou; Afkhami, Sam; Bavananthasivam, Jegarubee; Fritz, Dominik K.; D'Agostino, Michael R.; Vaseghi‐Shanjani, Maryam; Yao, Yushi; Jeyanathan, Mangalakumari
Abstract: In the past few years, our understanding of immunological memory has evolved remarkably due to a growing body of new knowledge in innate immune memory and immunity. Immunological memory now encompasses both innate and adaptive immune memory. The hypo‐reactive and hyper‐reactive types of innate immune memory lead to a suppressed and enhanced innate immune protective outcome, respectively. The latter is also named trained innate immunity (TII). The emerging information on innate immune memory has not only shed new light on the mechanisms of host defense but is also revolutionizing our long‐held view of vaccination and vaccine strategies. Our current review will examine recent progress and knowledge gaps in innate immune memory with a focus on tissue‐resident Mϕs, particularly lung Mϕs, and their relationship to local antimicrobial innate immunity. We will also discuss the impact of innate immune memory and TII on our understanding of vaccine concept and strategies and the significance of respiratory mucosal route of vaccination against respiratory pathogens. Graphical Abstract: Review on innate immune memory; focuses particularly on tissue‐resident Mϕs, anti‐microbial innate immunity, and vaccine strategies.